先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b=-3c=1

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/29 19:38:47
先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b=-3c=1
x){gu OzmlzڰJP(1(I780HLJ515uM@T1PPi';&$'$X;3l:AR U`Ja 0 HL4N!el_\g>#*|

先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b=-3c=1
先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b=-3c=1

先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b=-3c=1
-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc
=-1/2a^2b-3\2a^2b+3abc-a^2c+4a^2c-3abc
=-2a^2b+3a^2c
=-2×1×1+3×1×(-1/3)
=-2-1
=-3